Masa Depan Demokrasi Islam Di Indonesia - Nurul Huda; Abdul Rohman; Asep Badruzzaman (UIN Mataram, 2020)
This article discusses Islamic democracy in Indonesian democracy. Deliveries made by Islamic leaders have always been in the spotlight by the government. Apart from the government, the spotlight also came from foreign media, which reported that the Islamic figure incited the community. The question is, what is the ethical foundation of democracy in Indonesia? What is Islamic democracy like in Indonesian democracy? This research was conducted with a normative research method, qualitatively using literature study to obtain answers to the topics discussed. The answer was obtained that democracy in Indonesia is Pancasila democracy with the people as the highest authority. Furthermore, the values ​​of democracy in Islam contribute to democracy in Indonesia, such as justice, freedom of opinion, human rights, and others. This can be seen by examining the Medina Charter, which is a legal product during the leadership of the Prophet Muhammad SAW, where the Prophet Muhammad SAW emphasized deliberation as a means of resolving conflicts, both for believers and non-Muslims, and if they did not find common ground, the Prophet Muhammad as the messenger of Allah is the final decision holder. Likewise Indonesian democracy, prioritizing agreement in decision-making, through people's representatives, and the people as the owner of supreme sovereignty, always guarding these decisions.